Unveiling The Appeal of Wayang Jogja Night Carnival: An Analysis of Tourist Characteristics, Economic Impacts and Destination Evaluation - Mona Erythrea Nur Islami; Fian Damasdino; Nikasius Jonet Sinangjoyo; Amelia Lintang Mahiswara; Hary Hermawan (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2026)
The Wayang Jogja Night Carnival (WJNC) is a premier cultural street carnival in Yogyakarta that integrates traditional puppetry with modern technology. Despite its prominent role in destination branding, comprehensive studies balancing its socioeconomic benefits and urban management challenges remain limited. This study aims to analyze visitor demographics, economic impacts on local MSMEs, and evaluate the destination components using the 4A framework. A descriptive quantitative approach with a cross-sectional survey design was employed, gathering primary data from 487 randomly selected visitors and cluster-sampled local MSMEs during the event. Data were analyzed using descriptive statistics and cross-tabulation via SPSS. The findings reveal that visitors are predominantly female (57.1%) and dominated by Generation Z (50.3%). Economically, local MSMEs experienced a temporary boom, with daily turnover increasing by 150% to 300%. Evaluation of the 4A components indicates that 'attraction' scored the highest satisfaction (mean 4.45) , while 'amenities' scored the lowest due to limited sanitation facilities. Furthermore, the event induced traffic congestion within a 2-kilometer radius. In conclusion, WJNC significantly drives the local economy, but demands adaptive mobility management and upgraded public amenities for long-term sustainability. This research was institutionally supported and funded by the Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Sekolah Tinggi Pariwisata AMPTA Yogyakarta, with data facilitation provided by the Dinas Pariwisata Kota Yogyakarta.